HUBUNGAN SKOR PLASENTA AKRETA INDEKS (PAI) DENGAN KEJADIAN LUARAN PLASENTA AKRETA DI RSUD Dr. SOETOMO SURABAYA - DWI FADJAR MUHARDINI, NIM011511223041 (2017)
The number of cesarean section birth has increased from 5% to 20% over the last 20 years. The increased cesarean section rates were leading to increase placenta previa or accreta cases. One of the placenta accreta detection tools is Placenta Accreta Index (PAI). Some of placenta accreta cases had high score of PAI, therefore this study aims to determine the relationship between placenta accreta index score and placenta accreta output. The research design was cross sectional analytic by comparing between case groups and kontrol groups retrospectively. The samples of 60 mothers divided into two groups, 30 mothers with placenta accreta as case group and 30 mothers without placenta accreta as kontrol group, who selected by total sampling based on inclusion criteria. Data were taken from medical record by using collection sheets as instruments. Data were analyzed using Chi-Square test. The result of research showed that 80% of placenta accreta output (+) had PAI score ≥ 5, whereas 96.6% of placenta accreta output (-) had PAI score < 5. The statistical analytic results were obtained p (0,000) < 0.05 and C = 0.614 (0.60<C<0.799), which means there is significant correlation between placenta accreta index score and placenta akreta output significant with strong relationship level.